A Japanese Case of Lenz‐Majewski Syndrome With a Novel PTDSS1 Variant - Yasuko Kobari; Non Miyata; Jun Takayama; Naoya Saijo; Tomohisa Suzuki; Shigeo Kure; Atsuo Kikuchi; Gen Tamiya; Takumi Takizawa (Molecular Genetics & Genomic Medicine)
ABSTRACT Background Lenz‐Majewski syndrome (LMS) is a rare genetic disorder characterized by osteosclerosis, intellectual disability, characteristic facies, and distinct craniofacial, dental, cutaneous, and distal‐limb anomalies. Mutations in the PTDSS1 gene, which encodes one of the phosphatidylserines (PS) synthase enzymes, PSS1, have been identified as causative in LMS patients. These mutations make PSS1 insensitive to feedback inhibition by PS levels. Methods Whole genome sequence (WGS) was performed on a patient with congenital cutis laxa and her parents. PS synthase activity was analyzed in PTDSS1 mutant cDNA clones to evaluate functional alterations. Results A 5‐year‐old girl presented with congenital skin wrinkles and was initially diagnosed with congenital cutis laxa. She had bilateral inner ear hypoplasia, bilateral low‐frequency hearing loss, attention‐deficit/hyperactivity disorder, and mild intellectual disability. Physical examination revealed protruding ears, frontal bossing, and dental malalignment. A de novo heterozygous missense variant in the PTDSS1 gene, c.284G>A (p. Arg95Gln) was identified by WGS. Functional analysis indicated increased PS synthase activity, supporting the pathogenicity of this variant. Conclusions The patient's cutis laxa and facial features were consistent with LMS, though radiographic findings did not reveal the characteristic sclerosing bone dysplasia reported in previous cases. This observation suggests that LMS may have a broader phenotypic spectrum than previously recognized.